Quaternary functional semiconductor device-based temperature sensors for low and high temperatures (LTs, HTs) - Altindal Yeriskin, S.; Yildiz, K.; Dere, A.; Orman, Y.; Yakuphanoğlu, Fahrettin (Iop Publishing Ltd, 2024)
The Al-(Zn:Cd:Ni:TiO2)-pSi diodes with a ratio of 4;2;2;2 were fabricated and their possible current transport mechanisms (CTMs) were investigated between 80-380 K and +/- 4.5 V range using current-voltage (IV) measurements. The saturation-current (I-s), quality/ideality factor (n), and barrier-height (BH)/(Phi(bo)) values of the didoes were calculated from the forward-bias ln(I-F)-V-F curve as function of temperature. While the value of BH is increased with temperature, n value is decreased with increasing temperature. Non-linear behavior was observed in the Arrhenius or Richardson plot (RP) (ln(I-o/T-2) versus q/kT) at low temperatures (LTs). Also, the Richardson- constant (A*) calculated from the linear part of this plot is quite lesser than its theoretical- value (=32 A.(cm.K)(-2) for p-Si), and high values of n at LTs show an evident deviated from thermionic-emission (TE) theory. To explain this case; both the nkT/q-kT/q, Phi(bo) and n versus q/2kT curves were plotted to determine the other possible-CTMs and they show that both the tunneling and Double Gaussian - distribution (DGD) are more effective rather than TE. The obtained A* value from the modified RP by using the standard deviation from Phi(bo)-q/2kT plot is closer to its theoretical value. The energy-dependent curve of interface states or traps (N-ss) was calculated from the I-F-V-F characteristics by considering the voltage dependence of the BH and n for the studied temperature range and they generally decline with increase in temperature due to the rearrangement and structure of electrons at traps under the influence of temperature. All these results show that the fabricated The obtained results suggest that the fabricated Al-(ZnCdNiTiO2)-pSi diode can be used as a temperature - sensor in low and high temperature applications.
Keywords: current transport mechanisms (CTMs); temperature dependent; energy dependent of surface states (Nss); double-gaussian distribution of BH; temperature sensitivity